2006
DOI: 10.1093/jb/mvj012
|View full text |Cite
|
Sign up to set email alerts
|

MARCH-III Is a Novel Component of Endosomes with Properties Similar to Those of MARCH-II

Abstract: MARCH comprises a recently identified family of transmembrane RING-finger proteins which is implicated in diverse biological functions, such as immune regulation, protein quality control, and membrane trafficking. We previously identified MARCH-II, as a binding partner of syntaxin 6, which plays a role in endosomal protein transport. In this paper, we describe the cloning and characterization of MARCH-III which is the closest homolog of MARCH-II. It is broadly expressed at relatively high levels in spleen, col… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
37
0
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 43 publications
(41 citation statements)
references
References 36 publications
2
37
0
1
Order By: Relevance
“…The E3 ubiquitin ligase MARCH II is a direct interactor that together with the related MARCH III protein regulates Stx6 distribution (13,14). Overexpression of MARCH II redistributes Stx6 to peripheral puncta that are most likely endosomes, and which contain the SNARE partner Vti1a (13).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The E3 ubiquitin ligase MARCH II is a direct interactor that together with the related MARCH III protein regulates Stx6 distribution (13,14). Overexpression of MARCH II redistributes Stx6 to peripheral puncta that are most likely endosomes, and which contain the SNARE partner Vti1a (13).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the Habc domain of Tlg1p (the yeast orthologue of Stx6) binds to Vps51p, a component of the Vps-fifty-three (VFT)/Golgiassociated retrograde protein (GARP) tethering complex that mediates trafficking from endosomes to the late Golgi (9)(10)(11). Many binding partners for Stx6 have been identified, including the tethering factor early endosome autoantigen 1 (EEA1) (12), the RING finger E3 ubiquitin ligases MARCH II (13) and MARCH III (14), and FIG (fused in glioblastoma, also known as PIST (PDZ domain protein interacting specifically with TC10), CAL (CFTR associated ligand), GOPC (golgi-associated PDZ and coiled-coil motif containing) (15)(16)(17)(18). Most recently, GARP subunits have been shown to bind both the SNARE domain and the N-terminal domain (1-176) containing both the Habc and linker domains of Stx6 (19).…”
mentioning
confidence: 99%
“…Thus, the MARCH10a-associated structures are likely to be microtubules. The E3 activity of several of the MARCH proteins has been shown to contribute to their subcellular localization (17,24,27). To test if the E3 activity of MARCH10a has such an effect, a mutant FLAG-MARCH10a containing serine substitutions at the conserved catalytic cysteine residues (C641S and C644S; FLAG-RINGmut) was transfected into COS7 cells, and the localization was determined by immunofluorescence microscopy.…”
Section: Super-resolution Imaging Of March10 Localization With Three-mentioning
confidence: 99%
“…Transmembrane MARCH proteins mediate the ubiquitination and subsequent down-regulation of cell-surface immune regulatory molecules, such as major histocompatibility complex class II and CD86 (17,18,21). Other proposed functions include endoplasmic reticulum-associated degradation (22), endosomal protein trafficking (23,24), mitochondrial dynamics (25,26), and spermatogenesis (19). MARCH7 (also known as Axotrophin) and MARCH10 are predicted to have no transmembrane spanning region.…”
mentioning
confidence: 99%
“…Particularly, ubiquitination of major histocompatibility complex class I leads to its endocytosis and subsequent sorting to the MVB pathway for lysosomal degradation (18). Previously we have demonstrated that MARCH-II and -III are endosomal proteins bound to the SNARE protein syntaxin 6 and are involved in the regulation of endosomal trafficking (24,25). Hence, it is conceivable that the MARCH family could function in protein sorting and transport.…”
mentioning
confidence: 99%